The Role of Cybersecurity in Combating Cybercrime in Algeria: Prospects and Challenges - GUEDOUARI, Fatma Zohra; ALLOUACHE, Mehdi (Journal of Human Sciences, 2025)
This study aims to highlight the role of cybersecurity as a fundamental pillar in combating cybercrime at the national level, particularly in the context of the increasing technological advancements across all economic, cultural, social, and security sectors. Cybercrime is viewed as one of the adverse effects of advanced technology, posing a genuine challenge threatening the lives of individuals, communities, and national security.The study concludes that significant national efforts are being made to achieve cybersecurity in the fight against cybercrime by enacting relevant laws and establishing specialized structures for combating cybercrime in Algeria. Additionally, it emphasizes the necessity of international cooperation and governmental coordination to exchange information and develop joint strategies to address transnational cybercrimes, thereby contributing to a comprehensive cybersecurity framework that safeguards individuals, institutions, and nations.